Advances in tecnological development and present status of the spiny lobster (Panulirus argus) from egg to commecial size - Igarashi, Marco Antonio (Semina: Ciências Agrárias, 2010)
The purpose of this review is to sumarize the studies on culture of Caribbean spiny lobster (Panulirus argus). Spiny lobster became a highly valued marine organism, since then, have had a manifold increase over the years in Brazil. However, most fisheries are fully exploited, and one of the few ways to increase production is through aquaculture. Keeping the larval spiny lobster alive in the laboratory through these delicate stages is very difficult. The first complete culture of Caribbean spiny lobster from hatch to puerulus stage occurred in 2006 at Mie Prefectural Fisheries Station in Japan. This result reflects the increasing availability of information on optimal culturing conditions, such as optimal environmental parameters, feeding, and tank design. Still, there are significant problems to overcome in the establishment of large-scale culture of phyllosoma. These further challenges include the control of bacterial diseases and excessive aggregation of larvae, the use of prepared diets such as artificial foods, and the reduction of high operating costs. In addition possibilities for the present are exploitation of juveniles from densely populated areas and utilization of natural food resources as feed for the lobster. In conclusion it is possible farming juvenile spiny lobsters in growout system.